GAMBARAN TENAGA KESEHATAN REKAM MEDIS BERDASARKAN METODE WORKLOAD INDICATOR STAFF NEED (WISN) DI RUMAH SAKIT UMUM KUNINGAN MEDICAL CENTER - Rina Eka Aulia; M.H. Asiana Gabril; Riantina Luxiarti (Jurnal Kesehatan Mahardika, 2019)
Workload Indicator Staff Need (WISN) is a method of calculating the needs of real health human resources implemented in each health work unit. The purpose of this study is to describe the needs of Medical Record staff based on the WISN methodIn Kuningan Medical Center (KMC) Hospital. This research method is a descriptive survey research method, the population of this study is 8 medical records officers, and the sample is 8 patients and the sampling uses total sampling. The results were obtained from the WISN ratio of 10 people, namely: 3 outpatient registrations, 1 inpatient registration, 1 outpatient coding, 1 inpatient coding, 2 assembling people, and 2 filing people, so it can be concluded that there are advantages to outpatient registration and any shortages for assembling and filing. The suggestion of this research is that future research can use other methods.